1995
DOI: 10.1128/iai.63.10.3820-3826.1995
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic activity of the Bacteroides fragilis enterotoxin causes fluid secretion and intestinal damage in vivo

Abstract: Strains of Bacteroides fragilis that produce an enterotoxin have been implicated in diarrheal disease in farm animals and humans during the past decade. Our laboratory has purified and characterized this enterotoxin as a single polypeptide (M r , ϳ20,000). Recently, we used PCR to clone and sequence the enterotoxin gene from B. fragilis and showed that it exhibits significant homology with extracellular metalloproteases. Further studies showed that the purified enterotoxin has protease activity. To further cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(57 citation statements)
references
References 32 publications
0
57
0
Order By: Relevance
“…Since the infiltration of neutrophils occurs in vivo in response to enterotoxigenic B. fragilis [6,7], we investigated whether this phenomenon could be mediated by NF-kB activation in BFTstimulated intestinal epithelial cells. Our results revealed that BFT stimulation of the apical membrane of intestinal epithelial cells induced neutrophil transmigration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the infiltration of neutrophils occurs in vivo in response to enterotoxigenic B. fragilis [6,7], we investigated whether this phenomenon could be mediated by NF-kB activation in BFTstimulated intestinal epithelial cells. Our results revealed that BFT stimulation of the apical membrane of intestinal epithelial cells induced neutrophil transmigration.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal epithelial cells are structurally and functionally polarized in vivo. Since a significant infiltration of neutrophils occurs in vivo in response to enterotoxigenic B. fragilis infection [6,7], we investigated whether this phenomenon could be mediated by NF-kB activation using a polarized intestinal epithelial T84 cell line. By using an inverted monolayer system [26,27], the apical surface of the cultured monolayers was stimulated with BFT and…”
Section: Inhibition Of Nf-kb Signals Decreases Neutrophil Transepithementioning
confidence: 99%
See 1 more Smart Citation
“…BFT stimulates intestinal epithelial cell morphologic changes [3,5,6]. Histological examination revealed that the inoculation of ETBF or BFT to intestinal lumen caused mucosal inflammation characterized by the infiltration of neutrophils [6,7].…”
Section: Introductionmentioning
confidence: 98%
“…Enterotoxigenic Bacteroides fragilis (ETBF) has been shown to be associated with non-invasive diarrheal diseases in animals and young children [1][2][3][4][5], and B. fragilis enterotoxin (BFT), an approximately 20-kDa heat-labile metalloprotease, is regarded as a virulence factor for this diarrheal disease. BFT stimulates NF-jB activation and IL-8 secretion [6][7][8][9], which is predicted to lead to mucosal transmigration of neutrophils with release of prostaglandins (PG).…”
Section: Introductionmentioning
confidence: 99%